Análise de formulações explícitas do coeficiente de perda de carga em condutos pressurizados - Pimenta, Bruna Dalcin (2017)
One of the parameters involved in the design of pressurized hydraulic systems is the pressure drop of the pipes. This verification can be performed through the Darcy-Weisbach formulation, which considers a coefficient of loss of charge (f) that can be measured by the implicit Colebrook-White equation. However, for this determination it is necessary to use numerical methods. Numerous explicit approaches have been proposed to estimate the "f", with different precisions and complexity. Considering the above, the objective of this work is to analyze the explicit approximations of the pressure loss coefficient for pressurized conduits in relation to the Colebrook-White formulation, through the relative performance and error index, determining the most accurate ones so that they can replace the standard Implied for the turbulent flow regime. It was analyzed 29 explicit equations in the literature, determining the coefficient of loss of charge through Reynolds number values in the range of 4x10³ ≤ Re ≤ 108 and relative roughness of 10-6 ≤ Ɛ / D ≤ 5x10-2, obtaining 160 points for each equation, totaling 4800 points. Statistical analysis was performed by the performance index (Id) and the relative error (ER) of the explicit equations in relation to Colebrook-White. The equations of Chen (1979), Shacham (1980), Sonnad Goudar (2006), Buzzelli (2008), Vantankhah and Kouchakzadeh (2008), Fang et al. (2011) and Offor and Alabi (2016a) apply for the entire range of 4x10³ ≤ Re ≤ 108 and 10-6 ≤ Ɛ / D ≤ 5x10-2, and presented high “Id” and high precision, the latter being highlighted by extreme precision, which is indicated to replace the use of the Colebrook-White standard approximation.